2016
DOI: 10.1016/j.bbamem.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The biological response of cells to nanosecond pulsed electric fields is dependent on plasma membrane cholesterol

Abstract: Previous work from our laboratory demonstrated nanopore formation in cell membranes following exposure to nanosecond pulsed electric fields (nsPEF). We observed differences in sensitivity to nsPEF in both acute membrane injury and 24h lethality across multiple cells lines. Based on these data, we hypothesize that the biological response of cells to nsPEF is dependent on the physical properties of the plasma membrane (PM), including regional cholesterol content. Results presented in this paper show that depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…Lower cholesterol content corresponded to higher susceptibility to a μsPEF as measured by the viability of the cell population after exposure ( Figure 1A). Furthermore, as has been shown previously for nsPEF [28], we see an increased susceptibility of the MDA-MB-231 cells to a PEF when the cholesterol content of the membrane is pharmacologically reduced with acute exposure to methyl-β-cyclodextrin (MβCD; see Figure 1B). These observations are analogous to the ones made by Kraske and Mountcastle, albeit with the caution of not over generalizing the importance of cholesterol in PEF susceptibility.…”
Section: Ising Model To Represent Electrically Perturbed Lipid Membranessupporting
confidence: 81%
See 1 more Smart Citation
“…Lower cholesterol content corresponded to higher susceptibility to a μsPEF as measured by the viability of the cell population after exposure ( Figure 1A). Furthermore, as has been shown previously for nsPEF [28], we see an increased susceptibility of the MDA-MB-231 cells to a PEF when the cholesterol content of the membrane is pharmacologically reduced with acute exposure to methyl-β-cyclodextrin (MβCD; see Figure 1B). These observations are analogous to the ones made by Kraske and Mountcastle, albeit with the caution of not over generalizing the importance of cholesterol in PEF susceptibility.…”
Section: Ising Model To Represent Electrically Perturbed Lipid Membranessupporting
confidence: 81%
“…In this study, we show that cholesterol content in mammalian cells dictate their susceptibility to μsPEFs (Figure 1). As pointed out, such observations have also been made for nsPEFs [28]. In mammalian cells, cholesterol-rich ordered domains exist as shown in Figure 1C.…”
Section: Discussionsupporting
confidence: 71%
“…We hypothesized that as a result of nsPEFs, permeabilization of the ER membrane would allow for the indiscriminate passage of molecules into and out of the sensitive ER luminal environment [Schoenbach et al, ], changes in intracellular calcium concentration [Beier et al, ; Semenov et al, ], oxidative stress [Pakhomova et al, ], and potential ATP shortage. Other noted observations related to nsPEF exposure, such as dependence on membrane concentrations of cholesterol [Cantu et al, ], PIP2 activation and dynamics [Tolstykh et al, ], cytoskeletal disruption effects and plasma membrane reorganization [Thompson et al, ], and nuclear envelope structure changes [Thompson et al, ], have all been shown to alter UPR dynamics and cell metabolism [Bravo et al, ]. Consequently, this change in molecular environment would not allow for proper protein folding, generating ER stress and activation of the UPR.…”
Section: Resultsmentioning
confidence: 99%
“…A Marx bank capacitor system ( Fig. 1a), previously described (Ibey et al 2014;Cantu et al 2016), was used to generate the 600-ns unipolar pulse ( Fig. 1b).…”
Section: Exposure Systemmentioning
confidence: 99%